„Die Medizin ist eine soziale Wissenschaft“ – zum 200. Geburtstag von Salomon Neumann - Kuntz, Benjamin; Regneri, Günter; Berghöfer, Anne; Schmiedebach, Heinz-Peter; Beddies, Thomas (DMW - Deutsche Medizinische Wochenschrift, 2019)
Salomon Neumann (1819–1908) is one of the outstanding representatives of 19th century social medicine. As a medical reformer, statistician and city councilor, he made a significant contribution to improving social and hygienic conditions in Berlin. His most famous work was published in 1847 under the title “Die oeffentliche Gesundheitspflege und das Eigenthum” [Public Health and Property]. From 1859 to 1905, Neumann was active in the Berlin City Council for the improvement of the living conditions of the population. He was involved in the construction of municipal hospitals, supported the modernisation of sewage disposal, organised the Berlin censuses of 1861 and 1864 and was active in the field of health and social statistics. Not only was Neumann exposed to anti-Semitic reprisals during his lifetime, a foundation he founded to promote the science of Judaism was dissolved by the National Socialists in 1940. On the occasion of his 200th birthday, this article commemorates the life and work of the democratically minded and socially committed doctor and health politician. Salomon Neumann has rendered great services to social medicine in Germany.
Keywords: Salomon Neumann; Sozialmedizin; Reform